The Effect of Zinc-Proteinate Supplementation on the In Vitro Digestibility and Ruminal Fermentation in Goat - Gilbert Nathaniel; Tiara Annisa; Anis Muktiani; Dian Wahyu Harjanti; Widiyanto Widiyanto (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2021)
This study aimed primarily to investigate the effect of Zn-Proteinate (Zn-Prot) supplementation on in vitro rumen digestibility and rumen fermentation. This research used a completely randomized design with four treatments and four replicates. The experimental treatment was the supplementation of various levels of Zn-Prot (0; 12.5 ppm; 25 ppm, and 37.5 ppm) on a dry matter basis. Parameters determined were in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD), partial volatile fatty acid (VFA) (acetate, propionate, and butyrate), A/P ratio, CH4, and the efficiency of the conversion hexose to VFA. Data were analyzed using ANOVA. The results showed that goats fed with a diet supplemented with 25 ppm Zn-Prot had the highest IVDMD and IVOMD values. There was no significant effect on the VFA and CH4 concentrations, A/P ratio, and the efficiency of the hexose-VFA conversion within treatment groups. In conclusion, supplementing 25 ppm of Zn-Prot into the diet of dairy goat increase the dry matter and organic matter digestibility.